1994
DOI: 10.1136/oem.51.4.262
|View full text |Cite
|
Sign up to set email alerts
|

Case-control study of risk factors for disease in the neck and shoulder area.

Abstract: A case-control study was performed to elucidate the strength of the relation between musculoskeletal disorders in the neck and shoulders and physical, organisational, and psychosocial aspects of the work environment. Cases were identified as those persons who consulted a physician in a community in southern Sweden for new musculoskeletal disorders in the neck and shoulders during a study period from August 1988 to the end of October 1989. One hundred and nine cases were collected and clinically examined. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 12 publications
7
61
4
Order By: Relevance
“…The reproducibility of the diagnosis was demonstrated for 4 of the studies (18,35,37,38) and suggested in 2 others (39,63). Blinded assessment of outcome was explicitly declared in 5 studies (18,35,37,43,61), but may have occurred in several others by virtue of design or previously described methodology (19,38,58,65).…”
Section: General Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reproducibility of the diagnosis was demonstrated for 4 of the studies (18,35,37,38) and suggested in 2 others (39,63). Blinded assessment of outcome was explicitly declared in 5 studies (18,35,37,43,61), but may have occurred in several others by virtue of design or previously described methodology (19,38,58,65).…”
Section: General Findingsmentioning
confidence: 99%
“…Most of the studies achieved a high response rate, but, for a few Table 7. Summary of conclusions in relation to neck pain with palpation tenderness (tension neck syndrome or mixed neck-shoulder disorders with a preponderance of tension neck syndrome) 16 investigations of neck pain with tenderness (11 of these using tension neck syndrome as the disease label), 6 of neck pain with pain on neck movement (5 called cervical syndrome), 3 of thoracic outlet syndrome (all with very few cases), and 7 reports of mixed neck-shoulder disorder in which tension neck syndrome or neck pain with tenderness was diagnosed in >50% of the cases (35,38,41,50,62,64,65). Several studies reported on more than one outcome.…”
Section: General Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the pathophysiology of these disorders is still largely unknown, several risk factors such as force, precision and task stress have been identified (Ekberg et al 1994, Milerad and Ericson 1994, Arie¨ns et al 2001, Buckle and Devereux 2002.…”
Section: Introductionmentioning
confidence: 99%
“…The MSDs risk factors are frequently caused by physical job features such as repetitive work [6][7][8][9][10], work in extreme and static postures [8,11,12]and work with forceful arm and hand movements [13][14][15], which have been found to be associated with upper extremity disorders. Likewise, heavy lifting and forceful movements have also been found to be the cause of low back disorders [16], while another risk factor is on working in a forward bent position [17].…”
Section: Introductionmentioning
confidence: 99%